Ensaios sobre trajetória do câmbio, investimento direto estrangeiro e crescimento econômico no Leste Europeu e no Brasil - Moizinho, Luzélia Calegari Santos (2020)
This thesis analyzed the impact of the exchange rate trajectory and foreign direct investments in the economic growth of CESEE countries (Central, Eastern and Southeast Europe) and Brazil, based on the macroeconomic theory of the new developmentalism, or structuralism, which has as prerogatives the maintenance of a competitive exchange rate, in order to favor the manufacturing sectors of the economy and growth with internal savings. Using autoregressive methods with distributed lags (ARDL), which allow the dynamic analysis of cointegration in the short and long term, this thesis investigated the following problems: i. the relation of the exchange rate trajectory (misalignment and volatility) of effective real exchange rates and foreign direct investment (FDI) affect the economic growth of CESEE countries in the period from 1994 to 2018; ii. the impacts of commodity prices, FDI and export of natural resources on the exchange misalignment for CESEE countries from 1994 to 2018; and, iii. the relationship between exchange rate misalignments of the effective real exchange rate and foreign direct investment in Brazil's economic growth, from 1996 to early 2019. The analysis of the relationship between exchange rate misalignment and growth, corroborated the initial hypotheses that, overvaluation exchange rate causes restrictions on productive performance, since a sharp and long-lasting exchange rate overvaluation can break production chains and lead to deindustrialization, which is not easily reversed over time. Regarding the contribution of FDI to economic growth, the results at CESEE point to a positive relationship in the short and long term, which indicates that these countries are succeeding in attracting direct investments that are capable of providing catching-up strategies, improving levels of productivity, technology and industrial performance. In the Brazilian case, the cointegration did not present statistical significance, inferring that, according to the models proposed in this essay, the significant increase in FDI in the last decades did not interfere in the Brazilian economic performance. The descriptive analysis of the FDI trajectory in Brazil shows that, predominantly, these resources were directed to the service sectors and suggests that they did not help Brazil to increase the volume of exports. The influence of the variables of commodity prices, FDI and exploitation of natural resources in the exchange rate misalignment for CESEE countries was also identified. The results show that: i. in the short term, the increase in commodity prices is related to the overvaluation of the REER, while in the long term the relationship is reversed; ii. foreign direct investment in the short term undervalues REER and in the long run is in line with the overvaluation of REER; and, iii. the increase in the export of natural resources is statistically significant only in the long run, corroborating original theories that the discovery and exportation of these resources leads to exchange overvaluation.